Dependency Ratio and Economic Growth: Does Demographic Bonus Boost East Java’s Economy? - Ananda, Muhammad Rizqie; Pratomo, Devanto Shasta (Journal of Development Economic and Social Studies, 2026)
Economic growth is an indicator for assessing the development of a region. Economic growth is influenced by various factors, one of which is human capital. This study aims to determine the effect of independent variables, namely the demographic bonus, using data on the dependency ratio of regencies/cities in East Java during 2015–2024 with TPT, HDI, and investment as control variables. This study applies a quantitative approach using panel data from 38 districts/cities analyzed through panel data regression. The results show that the demographic bonus has boost East Java's economy.